DNA polymerase activities induced by polyoma virus infection of 3T3 mouse fibroblasts. - Närkhammar, M (1976)
Resting mouse 3T3 fibroblasts were stimulated to synthesize DNA either by infection with polyoma virus or by injection of fresh serum. Changes in the levels of DNA polymerase (alpha-, beta-, and gamma-enzymes) were measured in the cytoplasm and the cell nucleus. Both types of stimulation gave very similar increases for all three enzyme activities. In the cell nucleus, both alpha- and gamma-polymerases increased almost tenfold, whereas the beta-enzyme only was stimulated twofold. In the cytoplasm alpha- and gamma-polymerases increased two- to four-fold. Only insignificant amounts of the beta-enzyme were found in the cytoplasm.